Jenis Akad-Akad Pembiayaan Pada PT. BPRS Al-Wasliyah Kota Medan - Arif Kusnedi Saragih (Universitas 45 Surabaya, 2024)
The purpose of this study is to identify the various financial contracts that PT BPRS Alwasliyah Medan City has. A qualitative approach was used as the research methodology. Primary and secondary data are the sources of data. Interviews with PT managers and consumers served as the method of data collecting. BPRS City of Medan. The study done led to the conclusion that PT. BPRS Al-Washliyah in Medan City provides a range of finance contracts that adhere to the norms of Islamic sharia. The Finance Implementation Guidelines and Financial Services Authority Regulations (POJK), as well as other BPRS internal regulations, have been followed in accordance with established procedures and applicable fundamental financing legislation when it comes to the implementation of financing at BPRS.